KEMAMPUAN BAKTERI Achromobacter xylosoxidans DAN Arthtrobacter polychromogenes TERHADAP PENURUNAN TOTAL PETROLEUM HYDROCARBON (TPH) PADA TANAH TERCEMAR MINYAK BUMI DI BOJONEGORO - Lady Diana, ; Yuliani, (Matematika dan Sains, 2009)
The goal of research were to study the enfluence adding of Achromobacter xylosoxidans and Arthtrobacter polychromogenes and its combination to TPH value, P-available, N-total, and C/N ratio on the land polluted by petrolleum and to find the kind of bacteria that could optimally decrease TPH value, increase phosfat available and N total, and decrease C/N ratio. This research was experiment with completely randomized design using one treatment namely using Achromobacter xylosoxidans and Arthtrobacter polychromogenes with four replications. Data obtained were analyzed descriptively. The results of research showed that the adding A. Xylosoxidans, A. Polychromogenes and its combination could decrease the TPH value, increase P-availlabe and N total, and decrease C/N ratio. A. xylosoxidans could decrease TPH value optimally, while A. polychromogenes increase the N total and decrease C/N ratio effectively. The combination of A. xylosoxidans and A. polychromogenes could increase P-availlable optimally.